Penerapan The Dude Sebagai Monitoring System Untuk Optimalisasi Kinerja Infrastruktur Jaringan - Fairuz Furqon; Herman Saputra; Sahren Sahren (J-Com (Journal of Computer), 2026)
Abstract: The development of network infrastructure in higher education environments demands a monitoring system capable of detecting disruptions quickly and accurately. Royal University does not yet have an integrated and real-time network monitoring system, so network administrators often discover disruptions after receiving reports from users. This condition results in slow response to disruption handling and suboptimal network performance. This study aims to implement The Dude as a network monitoring system to support the optimization of Royal University's network infrastructure performance. The research method used is a qualitative approach with the stages of problem identification, literature study, system analysis, system design, implementation, and system testing. The monitoring system is implemented with The Dude Server architecture running on MikroTik CHR, while The Dude Client is used by the administrator via a laptop. The results show that the system is capable of performing network discovery, monitoring device status in real-time, displaying network topology visualization, recording monitoring history, and providing notifications when disruptions occur. System testing proves that all monitoring functions run according to the analyzed requirements. Thus, the implementation of The Dude is proven effective in increasing the speed of disruption detection, troubleshooting efficiency, and optimizing the network performance of Royal University. Keywords: mikrotik; network monitoring; network discovery; network optimization; the dude Abstrak: Perkembangan infrastruktur jaringan di lingkungan perguruan tinggi menuntut adanya sistem pemantauan yang mampu mendeteksi gangguan secara cepat dan akurat. Universitas Royal belum memiliki sistem monitoring jaringan yang terintegrasi dan real-time, sehingga administrator jaringan sering mengetahui gangguan setelah menerima laporan dari pengguna. Kondisi ini berdampak pada lambatnya respons penanganan gangguan serta kurang optimalnya kinerja jaringan. Penelitian ini bertujuan untuk mengimplementasikan The Dude sebagai sistem monitoring jaringan guna mendukung optimalisasi kinerja infrastruktur jaringan Universitas Royal. Metode penelitian yang digunakan adalah pendekatan kualitatif dengan tahapan identifikasi masalah, studi literatur, analisis sistem, perancangan sistem, implementasi, dan pengujian sistem. Sistem monitoring diimplementasikan dengan arsitektur The Dude Server yang berjalan pada MikroTik CHR, sedangkan The Dude Client digunakan oleh administrator melalui laptop. Hasil penelitian menunjukkan bahwa sistem mampu melakukan network discovery, memantau status perangkat secara real-time, menampilkan visualisasi topologi jaringan, mencatat histori monitoring, serta memberikan notifikasi ketika terjadi gangguan. Pengujian sistem membuktikan bahwa seluruh fungsi monitoring berjalan sesuai dengan kebutuhan yang telah dianalisis. Dengan demikian, implementasi The Dude terbukti efektif dalam meningkatkan kecepatan deteksi gangguan, efisiensi troubleshooting, dan optimalisasi kinerja jaringan Universitas Royal. Kata kunci: mikrotik; monitoring jaringan; network discovery; optimalisasi jaringan; the dude